Microscale Generation of Entangled Photons without Momentum Conservation - Okoth, Cameron; Cavanna, Andrea; Santiago-Cruz, T.; Chekhova, Maria (Physical Review Letters, 2019)
We report, for the first time, the observation of spontaneous parametric down-conversion (SPDC) free of phase matching (momentum conservation). We alleviate the need to conserve momentum by exploiting the position-momentum uncertainty relation and using a planar geometry source, a 6 μm thick layer of lithium niobate. Nonphase-matched SPDC opens up a new platform on which to investigate fundamental quantum effects but it also has practical applications. The ultrasmall thickness leads to a frequency spectrum an order of magnitude broader than that of phase-matched SPDC. The strong two-photon correlations are still preserved due to energy conservation. This results in ultrashort temporal correlation widths and huge frequency entanglement. The studies we make here can be considered as the initial steps into the emerging field of nonlinear quantum optics on the microscale and nanoscale.
CRIS-Team Scopus Importer:2020-02-21

Non-phase matched spontaneous parametric down conversion in ultra-thin lithium niobate - Okoth, Cameron; Santiago, Tomás; Cavanna, Andrea; Chekhova, Maria (Optics InfoBase Conference Papers, 2019)
We report the generation of entangled photon pairs via type-0 spontaneous parametric down conversion in ultra-thin lithium niobate in which momentum between the.
CRIS-Team Scopus Importer:2019-07-09

Photonic crystal fibers for generating three-photon states - Chekhova, Maria; Cavanna, Andrea; Taheri, Michael; Okoth, C.; Jiang, X.; Joly, Nicolas; Russell, Philip St. John (2017 Conference on Lasers and Electro-Optics, CLEO 2017 - Proceedings, 2017)
Direct decay of pump photons into triplets is an interesting but not-yet-realized nonlinear effect. We are exploring two approaches using photonic crystal fibers: a gas-filled hollow-core PCF and the recently designed hybrid solid-core PCF.
CRIS-Team Scopus Importer:2023-03-27

Progress toward third-order parametric down-conversion in optical fibers - Cavanna, Andrea; Hammer, Jonas; Okoth, Cameron; Ortiz-Ricardo, Erasto; Cruz-Ramirez, Hector; Garay-Palmett, Karina; U'Ren, Alfred B.; Frosz, Michael H.; Jiang, Xin; Joly, Nicolas; Chekhova, Maria (Physical Review A, 2020)
Optical fibers have been considered an optimal platform for third-order parametric down-conversion since they can potentially overcome the weak third-order nonlinearity by their long interaction length. Here we present, in the first part, a theoretical derivation for the conversion rate both in the case of spontaneous generation and in the presence of a seed beam. Then we review three types of optical fibers and we examine their properties in terms of conversion efficiency and practical feasibility.
CRIS-Team WoS Importer:2020-04-10

Separated Schmidt modes in the angular spectrum of biphotons - Borshchevskaia, N. A.; Just, F.; Katamadze, K. G.; Cavanna, Andrea; Chekhova, Maria (Laser Physics Letters, 2019)
We prepared qudits based on angular multimode biphoton states by modulating the pump angular spectrum. The modes were prepared in the Schmidt basis and their intensity distributions did not overlap in space. This allows one to get rid of filtering losses while addressing single modes and to realize a single-shot qudit readout.
CRIS-Team WoS Importer:2019-07-26